2018
DOI: 10.18805/ijar.b-877
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Rehabilitation of Wild Birds and Mammals

Abstract: Today, the ecosystem is being rapidly destroyed due to habitat loss, animal hunting, road construction, raising of transmission lines, general pollution, and agricultural activities, in addition to many other factors, all of which directly and indirectly affect wildlife. By necessity, rehabilitation units are available for the care and treatment of wild birds and mammals in need of life support. This paper discusses data collected regarding the treatment and rehabilitation of wild mammals and birds brought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…In seven of the twenty cases evaluated in our study; we could not find the aetiology of the fracture. Of the thirteen remaining cases in which the aetiologies were known, the pathological fractures were found to occur as a result of a forearm injury in five cases, as a result of falling from the nest in five cases, as a result of a car crash in two cases and as a result of malnutrition under captivity for a long time in one case, the results obtained were found to be in parallel with the results of previously conducted studies (Aslan et al 2018).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In seven of the twenty cases evaluated in our study; we could not find the aetiology of the fracture. Of the thirteen remaining cases in which the aetiologies were known, the pathological fractures were found to occur as a result of a forearm injury in five cases, as a result of falling from the nest in five cases, as a result of a car crash in two cases and as a result of malnutrition under captivity for a long time in one case, the results obtained were found to be in parallel with the results of previously conducted studies (Aslan et al 2018).…”
Section: Discussionsupporting
confidence: 79%
“…As a result of recently conducted evaluations, it has been found that extremity fractures are the most frequent injuries in wild birds brought to animal hospitals and rehabilitations centres (Rodriguez et al 2010;Choi et al 2016;Aslan et al 2018). The treatment of extremity fractures has a vital significance for wild birds.…”
mentioning
confidence: 99%
“…Wildlife rehabilitation data have been used for a variety of purposes, predominantly elucidating threats to native animals and examining associated outcomes (e.g. [2,[12][13][14][15][16][17][18][19][20]). Furthermore, studies have begun using these data to explore factors affecting release success, such as the life stage, condition, and sex of the animal (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates that the OC procedure allows obtaining and collecting adequate ej aculates, which can be used in assisted reproduction programs in captivity. Just as those obtained in the study carried out by Villaverde-Morcillo et al (2015), in which the semen characteristics of a single specimen of golden eagle trained to allow semen recovery through cooperative copulation are described, in this study, azoospermic ejaculates were observed at the beginning and end of the reproductive season; similarly, a variation in ejaculate volume, concentration and sperm motility was observed, indicating the high variability of ejaculates of the species; In which rescued specimens that cannot be returned to the wild can be integrated (Aslan et al, 2018). According to Starling (2013), the effectiveness of operant conditioning is linked to the learning capacity of each subject, the ability of the trainer to apply that type of training and the routine interaction with the subject.…”
Section: Seminal Indicatorsmentioning
confidence: 61%